Chronic Kidney Disease in Cats and the Risk of Total Hypercalcemia. (12th February 2017) - van den Broek, D.H.N.; Chang, Y.‐M.; Elliott, J.; Jepson, R.E.
Abstract : Background: Chronic kidney disease (CKD) is a common comorbidity in cats with hypercalcemia, but whether CKD is a risk factor for hypercalcemia is unclear. Hypercalcemia often is diagnosed based on total calcium concentration (tCa), which tends to underestimate the ionized calcium concentration (iCa) in cats. Objectives: Assessment of the performance of tCa for the diagnosis of ionized hypercalcemia, and exploration of factors influencing the relationship between iCa and tCa. Determination of risk factors for incident total hypercalcemia (ie, the development of hypercalcemia based on tCa during follow‐up). Animals: Records of a cross‐section (n = 477) and observational cohort (n = 367) of client‐owned cats with and without azotemic CKD from first opinion practice. Methods: Retrospective cross‐sectional and retrospective cohort study. The diagnostic accuracy of tCa as an index test for ionized hypercalcemia was evaluated, and risk factors for underestimation were explored by binary logistic and linear regression in a cross‐section of cats with and without azotemic CKD. Chronic kidney disease and clinicopathological variables were assessed as predictors of incident total hypercalcemia by both time‐invariant and time‐dependent Cox regression in a cohort of cats. Results: Specificity of tCa for identification of ionized hypercalcemia was high (100%), but sensitivity was low. Underestimation was associated with lower venous bicarbonate concentrations. Cats with CKD had increased risk for incident total hypercalcemia (hazard ratio, 4.29; 95% confidence interval, 1.96–9.37; P < .001). Higher tCa predicted incident total hypercalcemia in both azotemic and nonazotemic cats ( P < .001). Conclusions and Clinical Importance: Chronic kidney disease is a risk factor for incident total hypercalcemia, and most cats with increased tCa had concurrent ionized hypercalcemia. Higher baseline tCa predicts incident total hypercalcemia. Prospective studies assessing changes in iCa are warranted.